Integrin Crosstalk and Its Effect on the Biological Functions of the Trabecular Meshwork/Schlemm’s Canal - Jennifer A. Faralli; Mark S. Filla; Donna M. Peters; Donna M. Peters (Frontiers in Cell and Developmental Biology, 2022)
Integrins are a family of heterodimeric receptors composed of an α- and β-subunit that mediate cell-adhesion to a number of extracellular matrix (ECM) proteins in the Trabecular Meshwork/Schlemm’s canal (TM/SC) of the eye. Upon binding an ECM ligand, integrins transmit signals that activate a number of signaling pathways responsible for regulating actin-mediated processes (i.e phagocytosis, cell contractility, and fibronectin fibrillogenesis) that play an important role in regulating intraocular pressure (IOP) and may be involved in glaucoma. An important function of integrin-mediated signaling events is that the activity of one integrin can affect the activity of other integrins in the same cell. This creates a crosstalk that allows TM/SC cells to respond to changes in the ECM presumably induced by the mechanical forces on the TM/SC, aging and disease. In this review, we discuss how integrin crosstalk influences the function of the human TM/SC pathway. In particular, we will discuss how different crosstalk pathways mediated by either the αvβ3 or α4β1 integrins can play opposing roles in the TM when active and therefore act as on/off switches to modulate the cytoskeleton-mediated processes that regulate the outflow of aqueous humor through the TM/SC.